Uczenie działań komunikacyjnych poprzez bezpośrednią instrukcję - Nowicka, Agnieszka (Wydawnictwo Państwowej Wyższej Szkoły Zawodowej w Koninie, 2008)
The article focuses on teaching and learning conversational actions in English as a FL in direct instruction based on the guided discovery observation of discourse models such as transcribed video discus- sions and conversations. The aim of the task is to develop students’ communicative awareness, which in turn allows them to find in dis- course those communicative actions which suit their communicative style and contribute to the development of their personal communic- ative competence. Discourse observation tasks are accompanied by project tasks such as classroom role plays and discussions and inter- views with a foreigner in which students are expected to produce the observed communicative actions. The paper is based on a case study of one student’s performance in the selected two types of tasks, dis- course observation tasks and an interview with a foreigner.
Keywords: analiza konwersacyjna; dydaktyka języka angielskiego jako JO; bezpośrednia instrukcja; obserwacja dyskursu